Managing Distrust-Induced Risk with Deposit in Supply Chain Contract Decisions - Guanghua Han; Ming Dong; Qi Sun (The Scientific World Journal)
This paper studies the trust issue in a two-echelon supply chain information sharing process. In a supply chain, the retailer reports the forecasted demand to the supplier. Traditionally, the supplier’s trust in the retailer’s reported information is based on the retailer’s reputation. However, this paper considers that trust is random and is also affected by the reputation and the demand gap. The supplier and retailer have been shown to have different evaluations regarding the degree of trust. Furthermore, distrust is inherently linked to perceived risk. To mitigate perceived risk, a two-stage decision process with an unpayback deposit contract is proposed. At the first stage, the supplier and the retailer negotiate the deposit contract. At the second stage, a Stackelberg game is used to determine the retailer’s reported demand and the supplier’s production quantity. We show that the deposits from the retailer’s and supplier’s perspectives are different. When the retailer’s reported demand is equal to the supplier’s forecasted demand, the retailer’s evaluation of the deposit is more than that of supplier’s. When the retailer’s reported demand is equal to the retailer’s forecasted demand, the deposit from the retailer’s perspective is at the lowest level.